O Ensino Superior e o papel do TCC na formação dos alunos: comparação entre a graduação em tecnologia em informática e o bacharelado em Ciência da Computação - Neves Filho, Luiz Alberto (2016)
This study presents an overview of the current model of higher education, from which training opportunities at the university are discussed. We analyzed aspects and social implications expressed in the works of completion of higher education (TCC) in computer science from a private institution, and which constituted a source for identification and examination of the training provided to students, considering its political content and concern with social issues, which could reveal traits that point to autonomy. The institution is investigated in São Paulo and has five campuses. Data were extracted from the matrices and curriculum guidelines for such courses present in educational legislation, and topics that are the rationale, objectives and conclusions of each TCC selected for analysis. The results indicates that although the students are obliged to proceed according to the institution's standards - role established courses on the needs of the labor market and technological innovation - yet their work displays features of consciousness that we must act professionally given social problems. Therefore, the graduates of these computer courses were trained to adapt to the social and economic order, but are sensitive to the limits that prevent the improvement of quality of life for all individuals, which may mean some resistance to the impositions made to them in throughout his school career. The theoretical framework adopted in this research is linked to the contributions of the authors of the Critical Theory of Society, especially Theodor Adorno, Herbert Marcuse, Walter Benjamin and Max Horkheimer